COMPARATIVE STUDY ON THE IMPACT OF OBSERVING IMAGE-BASED ADMINISTRATIVE MAPS ON THE LEVEL OF SPATIAL THINKING UNDERSTANDING AMONG THE COMMUNITY - Nezar, Riyad Bariq; Astriati, Nuraini; Christanto, Ludovicus Manditya Hari (Universitas Tanjungpura, 2024)
This research aims to measure whether there are differences in the level of spatial thinking in villagers who have and have not observed the Image-Based Administrative Map of Rasau Jaya Tiga Village. This research uses a comparative method with a quantitative form of research. The population in this study was the Rasau Jaya Tiga village community, and the sample used consisted of 60 officials or officeholders in Rasau Jaya Tiga Village. The data source used was obtained directly through the results of the respondents questionnaire answers. The research results show that people who have ever observed a map have an average value of 126.7 or 79.2% of the total maximum score, while people who have never observed a map have an average value of 123.8 or 75.6%. The results of this research were processed using the Independent Sample T-Test, with the data processing results obtaining a significance value of 0.005 or smaller than the Î± value (0.005 0.05), which means that Ha is accepted. So, it can be concluded that there is a significant difference between the level of spatial thinking of people who observe image-based administrative maps and people who never observe image-based administrative maps in Rasau Jaya Tiga Village.